AB1089-HPR Perceptions of Patients with Rheumatoid Arthritis about Predictive Testing for Treatments: A Qualitative Study. (15th July 2016) - Kumar, K.; Cordingley, L.; Maskell, D.; Nair, N.; Barton, A.
Abstract : Background: Rheumatoid arthritis (RA) is a long term condition that requires early treatment to control symptoms and improve long-term outcomes. 1, 2 . Identifying biomarkers predictive of treatment response offers an opportunity to improve clinical decisions about which treatment to recommend in patients 3 . For this, we should take into account patients' perspective of these tests and that requires an understanding of the range of effects that predictive testing can have on RA patients. This study explored the factors that might influence a patients' decision to agree to tests using a qualitative approach. Objectives: To explore the factors that might influence a patients' decision to agree to tests. Methods: A qualitative study was undertaken in which explorative focus groups were conducted with RA patients from Manchester, Birmingham and London, UK. Semi-structured interviews about their perceptions of the use of tests to predict response to treatments were performed. Interviews were audio-recorded, transcribed verbatim and analysed using thematic analysis. 4 Results: Interviews were conducted with 16 patients. [13 female, age ranges: 26–80 years old, disease duration: 3–34 years]. Five interlinking themes influenced how RA patients would make decisions about predictive tests: [1] Perceptions surrounding the use of synovial biopsy and/or blood tests: [2] Perceptions surrounding the use of synovial biopsy vs blood test: [3] Utility of the test to manage expectations: [4] The stages of illness on decision making for predictive testing: [5] Understanding the predictive tests in clinic. Conclusions: Besides supporting clinical decision making, the development of predictive testing in RA is supported by patients. Patients recommended that additional support should be offered to help them cope with results that might not accurately predict response. Developing strategies which communicate risk information about predictive testing effectively while reducing the psychological burden associated with this information is essential. References: Symmons D, Turner G, Webb R, Asten P, Barrett E, Lunt M et al. The prevalence of rheumatoid arthritis in the United Kingdom: new estimates for a new century. Rheumatology (Oxford) 2002; 41(7):793–800. Smolen JS, Landewe R, Breedveld FC, Buch M, Burmester G, Dougados M et al. EULAR recommendations for the management of rheumatoid arthritis with synthetic and biological disease-modifying antirheumatic drugs: 2013 update. Ann Rheum Dis 2014; 73(3):492–509. Gonzalez-Alvaro I, Ortiz AM, Seoane IV, Garcia-Vicuna R, Martinez C, Gomariz RP. Biomarkers predicting a need for intensive treatment in patients with early arthritis. Curr Pharm Des 2015; 21(2):170–181. Dixon-Woods M, Agarwal S, Jones D, Young B, Sutton A. Synthesising qualitative and quantitative evidence: a review of possible methods. J Health Serv Res Policy 2005; 10(1):45–53. Disclosure of Interest: None declared